2000
DOI: 10.1002/1097-0185(20001101)260:3<294::aid-ar66>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Nerve fiber composition of the intracranial portion of the oculomotor, trochlear, and abducens nerves in the sheep

Abstract: In the present investigation, the fiber content and the diameter spectra of the intracranial portion of the three oculomotor nerves (oculomotor, trochlear, and abducens nerves) were analysed in sheep by light and electron microscopy. It was determined that up to 14.98% of fibers in the oculomotor nerve, 17.01% in the trochlear nerve, and 11.87% in the abducens nerve were unmyelinated. The myelinated fibers showed a bimodal distribution in their size spectrum in all three nerves, with a majority of large myelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 11 publications
4
13
1
Order By: Relevance
“…In sheep, Berardinelli et al. () examined the composition of the intracranial portion of nerves III, IV and VI, determining the number, size and percentage of myelinated and unmyelinated fibres, as did Hildebrand et al. () for nerves IV and VI in the cat.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In sheep, Berardinelli et al. () examined the composition of the intracranial portion of nerves III, IV and VI, determining the number, size and percentage of myelinated and unmyelinated fibres, as did Hildebrand et al. () for nerves IV and VI in the cat.…”
Section: Discussionmentioning
confidence: 99%
“…As was previously carried out by Berardinelli et al. () from the total ultrathin cross sections, 25% was analysed in randomly chosen squares, and the number of unmyelinated fibres was counted. Their cross‐sectional area and maximum and minimum diameter were calculated.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Compression of pain sensory afferent fibres of the ophthalmic division of the f f trigeminal nerve present in the third cranial nerve by the aneurysm is alleged by some as the cause of the orbital headache [25]. In this regard, Berardinelli et al [26] identified unmyelinated fibres in the oculomotor, trochlear and abducens nerves, and suggested that they are sensory in nature and are involved in the transport of pain signals arising from the trigeminal territory. Bortolami et al [27] demonstrated that trigeminal neurons send their process centrally through the oculomotor nerve, which supplies the extra-ocular muscles, the cornea, and the superior eyelid, and contains neuropeptides (substance P, calcitonin gene-related peptide and cholecystokinin) that are usually associated with pain sensation.…”
Section: Discussionmentioning
confidence: 99%